Experiment-Based Study of Heat Dissipation from the Power Cable in a Casing Pipe - Romuald Masnicki; Janusz Mindykowski; Beata Palczynska (Energies, 2022)
The paper deals with the important challenges in terms of electricity transmission by means of underground cable lines. The power cable’s performance is characterized by an ampacity that represents its maximum electric current-carrying capacity. The ampacity of power cables depends on their ability to diffuse the heat generated by the current flow into the environment. In the performed research, the analysis of the efficiency of heat dissipation from the cable is based on the measurement of temperatures at selected points in individual sections of the cable. As a consequence, the proposed test stand and applied research methodology are vital for the experimental evaluation of the analyzed thermal phenomena in the investigated underground cable lines. The research program covers an in-depth analysis based on the results related to the vital parameters of the investigated cable. The experimental methodology was used to analyze the influence of the properties of the medium surrounding the cable on its temperature, and thus on the ampacity of the cable. A novelty of this paper concerns the carrying out of the experimental laboratory research with actual measurements of the temperature distribution in specific points of the casing pipe based on the original test stand. The paper presents the novel concept of the developed stand for testing heat dissipation from the cable in a casing pipe with pipe sections filled with various media, equipped with a power supply system ensuring easy control of the power dissipated in the cable. The preliminary results of the comparative tests, in which the temperature distribution in the sections of the casing pipes was recorded, indicate that the findings are satisfactorily consistent with the assumptions related to the purpose of the research. The use of appropriate materials surrounding the cable contributes to more effective heat dissipation, and as it has been shown for the examined case in originally planned and conducted tests, it can lower the cable temperature by more than 20 °C, contributing to a significant increase in the ampacity of the cable. For example, it was recorded that for different media filling the pipes, the cable reached 30 °C with different currents flowing through cable of 60 A and 120 A, respectively.